Effect of the Seasonal Climatic Variations on the Accumulation of Fruit Volatiles in Four Grape Varieties Under the Double Cropping System - Lu, Hao-Cheng; Chen, Wei-Kai; Wang, Yu; Bai, Xian-Jin; Cheng, Guo; Duan, Chang-Qing; Wang, Jun; He, Fei (Frontiers in Plant Science, 2022)
The double cropping system has been widely applied in the subtropical viticultural regions. In the two-year study of 2014-2015, four grape varieties were selected to analyze their fruit volatile compounds in the four consecutive seasons in the Guangxi region of South China, which had a typical subtropical humid monsoon climate. Results showed that berries of winter seasons had higher concentrations of terpenes, norisoprenoids, and C6/C9 compounds in ‘Riesling’, ‘Victoria’, and ‘Muscat Hamburg’ grapes in both of the two vintages. However, in the ‘Cabernet Sauvignon’ grapes, only the berries of the 2014 winter season had higher terpene concentrations but lower norisoprenoid concentrations than those of the corresponding summer season. Pearson correlation analysis showed that temperature was the main climate factor affecting volatile compounds between seasons. Hexanal, γ-terpinene, terpinen-4-ol, cis-furan linalool oxide and trans-pyran linalool oxide were all negatively correlated with the high-temperature hours in all of the four varieties. Transcriptome analysis showed that the upregulated VviDXSs, VviPSYs, and VviCCDs expressions might contribute to the accumulations of terpenes or norisoprenoids in the winter berries of these varieties. Our results provided insights into how climate parameters affected grape volatiles under the double cropping system, which might improve the understanding of the grape berries in response to the climate changes accompanied by extreme weather conditions in the future.